The Use of Direct Transfer Method on Embryo Cryopreservation in Dairy Cattle - Iman Supriatna; Tuty Laswardi yusuf; Bambang Purwantara; Gozali Moekti; Lies Parede Hernomoadi (Media Veteriner, 1999)
The experiment was carried out to study the use of direct transfer method in embryo cryopreservation by using two cryoprotectants and the effectivity of various concentrations of sucrose during cryoprotectant removal. Eighty-fourmorula stage embryos were divided equally into two groups and were treated by using 1.5 M ethylene glycol (EG) and 1.5 M 1,2-propanediol as cryoprotectant. The embryos were frozen using programmable embryo freezing machine on step by step decreasing temperature. Frozen embryos were thawed and cryoprotectants were removed either without sucrose (0 M) or with sucrose in concentration of 0.2 M, 0.4 M and 0,8 M. The results showed that the quality of the thawed embryos cryopreserved using 1.5 M EG was better than that using 1.5 M PROH. The survival rate on the embryos cryopreserved with 1.5 M EG (92.8%) was higher than 1.5 M PROH (78.6%) (P0.05). The viability of embryos exposed to 0 M, 0.2 M, 0.4 M and 0.5 M sucrose were 80.0, 80.8, 90.9 and 81.80% respectively. In contrast, by using 1.5 M PROH, rehydration with 0.4 M (83.3%) and 0,8 M (90.0%) sucrose was significantly better compared to those without (22.2%) or with 0.2 M (36.3%) sucrose (p